An endodontic emergency situation with airborne contagious diseases around: Situasi darurat endodontik dengan penyakit menular melalui udara sekitar - Lestari Hardianti Sugiaman; Noor Hikmah; Nurhayaty Natsir; Juni Jekti Nugroho; Wahyuni Suci Dwiandhany; Christine Anastasia Rovani (Makassar Dental Journal PDGI Makassar, 2023)
mergency endodontics account for one-third of all dental emergencies. Most cases can only be resolved if the dentist can inter-act directly with the patient. One of the airborne infectious diseases that needs attention is Covid-19, dental procedures have a high risk of transmitting the disease. Therefore, emergency endodontics during the pandemic is a big challenge. This paper re-views how to handle endodontic emergencies in the pandemic era. Teledentistry is one of the options as a first step to solve and help the patient's problem. For emergency endodontic interventions, after teleconsultation, dentists can plan endodontic treat-ments such as pulpotomy, pulpectomy, or incision and drainage, with proper control protocols to prevent transmission during the visit. It is concluded that emergency endodontics has a much higher risk of transmission. Reducing treatment time and ex-posure control are ways to reduce the risk of coronavirus spread during endodontic treatment. Following proper protocol pro-cedures in treating patients is a must, so as to protect many people.